Giuseppe Pasta (1742–1823) and the Courage in Medicine. - Sganzerla, Erik Pietro; Riva, Michele Augusto (Medicina Historica, 2022)
This paper examined an often-forgotten medical essay, written by the Italian physician Giuseppe Pasta (1742–1823) in 1792, that first underlined the importance of the psychic and emotional components in doctor-patient relationship. We analyzed the contents of the essay “Del coraggio nelle malattie” (“On Courage in Diseases”) by Pasta, highlighting the innovative aspects of the work and contextualizing them to the historical period in which the text was written. In his essay, Pasta states to be unable to explain the effects of the soul (or spirit) on human body. He considers the Courage as the most noble and most powerful of the feelings and the most necessary to sick people. In his opinion, doctors should instill Courage in their patients, counteracting all those negative feelings that could reduce it. Also in a desperate state, the confidence of the patients in their doctor is enough to give courage to them. There are illnesses which can be cured only with words; so a good doctor should spend all the necessary time with the patients in order to induce in them – through verbal and non-verbal means – positive reactions and courage in dealing with their state. In conclusion, the work of Giuseppe Pasta may be one of the first texts that analyzed the psychic and emotional components in doctor-patient relationship.